Pengaruh Kualitas Produk, Citra Merek Dan Celebrity Endorser Terhadap Keputusan Pembelian Smartphone Melalui Minat Beli Sebagai Variabel Intervening - Retry Dewi (Jurnal Administrasi Bisnis Fisipol Unmul, 2019)
The purpose of this study is to determine the variable product quality, brand image and celebrity endorser partially to the purchase decision of a smartphone’s, to determine the variable product quality, brand image and celebrity endorser partially on the purchase intention of a smartphone’s, as well as to determine the variable product quality, brand image and celebrity endorser partially on the purchase decision a smartphone’s through purchase intention as an intervening variable. The method used uses a quantitative research approach. The sample in this study 100 students of Muhammadiyah of University Ponorogo. The sampling technique using cluster rondom sampling. The result of this are the variable product quality, brand image and celebrity endorser partially affect the purchase decision of a smartphone’s, the variable product quality, brand image and celebrity endorser partially affect the purchase intention of a smartphone’s, as well as to determine the variable product quality, brand image and celebrity endorser partially affect on the purchase decision a smartphone’s  through purchase intention as an intervening variable.